MODEL RASIONAL DAN MODEL INKREMENTAL DALAM ANALISIS KEBIJAKAN PUBLIK: SEBUAH KAJIAN LITERATUR - Dian Oktaviani; Sabran; Sri Susmiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Public policy analysis is an important process in formulating and evaluating policies that affect society at large. In public policy studies, various analytical models are used to understand the decision-making process, including the rational model and the incremental model. This study aims to examine, through a literature review, the concepts, characteristics, and comparison between the rational model and the incremental model in public policy analysis. The research method used is a literature review by analyzing various academic sources such as books and relevant scientific articles. The results of the study show that the rational model emphasizes a systematic, comprehensive decision-making process based on optimal analysis of various policy alternatives. Meanwhile, the incremental model emphasizes gradual and realistic policy changes by considering limitations in information, time, and resources. This study concludes that both models have their own strengths and limitations; therefore, in practice, they are often used in a complementary manner in public policy analysis. Thus, understanding these two models is important for policy analysts in order to produce policies that are effective and adaptive to social dynamics.